Psychosocial impact of penile carcinoma - Audenet, François; Sfakianos, John P. (Translational Andrology and Urology; Vol 6, No 5 (October 26, 2017): Translational Andrology and Urology (Management of Penile Cancer), 2017)
Penile carcinoma is a rare malignancy with a potential for local invasion and regional/distant extension. Penile cancer can be cured in over 80% of cases if diagnosed early. However, local treatment, although potentially lifesaving, can be mutilating and devastating for the patient’s psychological well-being. In patients with long-term survival after penile cancer, sexual dysfunction, voiding problems and cosmetic penile appearance may adversely affect the patient’s quality of life. Although there is little data in the literature about psychosocial impact of penile carcinoma, organ-preserving treatment seems to allow for better quality of life and sexual function and should be offered to all patients whenever feasible.